Processos morfogenéticos e condicionantes associados aos eventos de entulhamento dos fundos de vales de afluentes do médio/baixo rio Paraopeba/MG - Alex de Carvalho (2014)
In recent decades, many studies have sought to understand the evolution of relief in the central of Minas Gerais through the interpretation of levels and depositional sequences present in the fluvial valleys of the main rivers. These studies are focus on mountain regions such as the Quadrilátero Ferrífero and the Serra do Espinhaço, where the riches of its depositional levels has allowed the interpretation of the role of litho-structural and neotectonics evolution of the fluvial dynamics and relief. The Paraopeba river basin has few studies in fluvial geomorphology, which treats specifically of its high and part of its middle course, located in the Quadrilátero Ferrífero and/or on its edges. In its middle and lower course, the small amount of depositional levels it´s a factor that complicates the interpretations of evolution of the fluvial dynamics and of the relief. Recently, a geological mapping identifies thick alluvial sequences, in the context of the bottom valley in Paraopeba river and its main affluents. These fluvial deposit of the valley bottom correspond to plains and terraces heavily exploited by mining. In this dissertation are investigated the morphogenetic processes and geomorphological context associated with the genesis, evolution and spatial organization of thick sedimentary packages present in the bottom river of the valleys affluents of middle / lower Paraopeba-MG. The study was conducted from: i) Identification, mapping and characterization of depositional sediments and related levels: ii) dating the sedimentary through the technique of optically stimulated luminescence (OSL); iii) and morphometric analysis of watersheds and drainage networks (Rr, Is, Dd, FABD and RDE). The most basins analyzed were identified up to three dispositional levels: a floodplain (N1), a level of terrace (N2) and depositional level mischaracterized by colluvial deposition (N3). The analysis of the spatial organization of granulometric composition and arrangement of depositional these levels allowed the proposition, at least four depositional events, which may be associated with tectonic control and litho-structural. The oldest depositional event its represented by N3, which are indications of deposition environments with greater energy. The following two events are represented by N2: N2 medium courses would be the record of an event of regional depositional in the Lower Rio Paraopeba basin and N2 of the lower courses of the affluents of the right bank of the Paraopeba river would be the record of a depositional event after the formation of the N2 medium courses. The last event is represented by the current line up of N1 in the lower reaches of the affluents of all Paraopeba river studied in this dissertation. There is also the formation of N1 and N2 in the upper courses of the Ribeirão das Lajes and Ribeirão do Ouro and of the levels N1 the medium courses of all affluents, which may represent events chronologically depositional distinct. The control tectonics is responsible for uplift and/or tilting that are evidenced by morphometric parameters, staggered depositional levels, river catches and drainage organizations. This control is favored by the rich structural framework inherited from Transamazônico and Brasiliano cycles, with faults and shear zones reactivated over the time geological. The organization of deposits is related to lithological control by basic dikes and quartz veins (cataclasite), which acts like local levels as basis for certain segments of watercourses and preserve the N2 and N1 in differentiated altimetric heights. According to the results of OSL dating, the depositional event 2 occurred between 17,600 ± 2,780 and 15,800 ± 2,580 BP, the event depositional of N2 in the upper courses of streams Lajes and Ouro occurred between 6.250 ± 1.100 and 2.850 ± 420 BP and depositional event 3 occurred between 2750 ± 420 and 1,250 ± 190 BP.